Visual Design Elements for Dyslexia-Friendly Reading Materials: A Systematic Literature Review - Elma, Khalda Rafifah; Rachmawanti, Ranti; Machfiroh, Runik (AL-ISHLAH: Jurnal Pendidikan, 2026)
Dyslexia is a specific learning disorder that affects word recognition, reading fluency, and text comprehension. Although previous systematic reviews have discussed dyslexia-related reading interventions and typographic factors, limited synthesis has integrated typography, layout, color contrast, and illustrations into practical visual design guidelines for children’s reading materials. This study aimed to identify visual design elements that support reading accessibility for children with dyslexia and to formulate evidence-based guidelines for classroom use. A Systematic Literature Review was conducted using the PICO framework and PRISMA protocol. Articles published between 2010 and 2025 were searched in five reputable international academic databases. Studies were included when they examined visual design elements in relation to dyslexia, child readers, readability, reading orientation, visual comfort, or comprehension. Studies were excluded when they were not empirical, did not focus on dyslexia, involved adult participants only, or were unavailable in full text. The quality of eligible studies was appraised using predefined criteria covering relevance, methodological clarity, data validity, and reporting transparency. Twenty-one articles met the inclusion criteria. The most consistent findings indicate that increased font spacing, adequate line spacing, simple layouts, clear text hierarchy, and moderate contrast improve readability, reading orientation, and visual comfort. Color and illustrations showed supportive effects when used selectively and without visual distraction. This review proposes Visual Design Guidelines for Dyslexia-Friendly Reading Materials that can guide teachers, designers, and publishers in preparing worksheets, classroom handouts, textbooks, and digital reading materials. The review also identifies research gaps related to classroom implementation and empirical validation of these design guidelines.